Dependence of reactions of the external respiratory system in athletes on the orientation of the training process - Kanyhina, S. M.; Potapenko, M. S.; Kurilets, L. O.; Канигіна, Світлана Миколаївна; Потапенко, Марина Станіславівна; Курілець, Лілія Олегівна; Каныгина, С. Н.; Потапенко, М. С.; Курилец, Л. О. (Запорізький державний медичний університет, 2021)
Issues of improving the functional training (different orientation of the training process) of athletes due the development of the respiratory system, including the respiratory system, as well as increasing the body’s resistance to hypoxic stress remain extremely relevant at the present stage of sport development. The aim of the study is to investigate the peculiarities of the reaction of the external respiratory system in athletes, depending on the orientation of the training process. Materials and methods. The study involved 104 athletes (84 men and 20 women) skill level from CMS to IMS: 63 – athletes, who developed mainly endurance quality (triathletes, swimmers, long-distance runners, rowing), 31 – strength quality (weightlifters, powerlifting, weightlifting), 10 – speed quality (runners sprinters). The mean age of the athletes under study was 21.75 ± 3.32 years. Among them there are international masters of sports (IMS) – 2 athletes, masters of sports (MS) – 25, candidates for master of sports – 48, athletes of 1 degree – 29. Computer spirometric examination was performed for all athletes using the spirographic complex “Spirocom” produced by LLC “KHAI-Medica” in Kharkiv in accordance with existing recommendations. Питання підвищення функціональної підготовки (різної спрямованості тренувального процесу) спортсменів шляхом розвитку респіраторної системи, зокрема системи зовнішнього дихання, а також підвищення стійкості організму до гіпоксичного навантаження залишаються надзвичайно актуальними на сучасному етапі розвитку спорту. Мета роботи – вивчити особливості реакції системи зовнішнього дихання у спортсменів залежно від спрямованості тренувального процесу. Матеріали та методи. У дослідження залучили 104 спортсменів (84 чоловіки і 20 жінок): 63 атлети, які розвивали переважно якість витривалості, 31 – якість сили, 10 – якість швидкості. Середній вік обстежених становив 21,75 ± 3,32 року. Серед обстежених – 2 майстри спорту міжнародного класу (МСМК), 25 майстрів спорту (МС), 48 кандидатів у майстри спорту, 29 спортсменів 1 розряду. Комп’ютерне спірометричне дослідження виконали всім спортсменам на спірографічному комплексі «Спіроком» (ТОВ «ХАІ-Медіка», м. Харків) відповідно до рекомендацій. Вопросы повышения функциональной подготовки (различной направленности тренировочного процесса) спортсменов за счет развития респираторной системы, в том числе системы внешнего дыхания, а также повышения устойчивости организма к гипоксическим нагрузкам остаются чрезвычайно актуальными на современном этапе развития спорта. Цель работы – изучить особенности реакции системы внешнего дыхания у спортсменов в зависимости от направленности тренировочного процесса. Материалы и методы. Обследовали 104 спортсмена (84 мужчины и 20 женщин): 63 атлета, которые развивали преимущественно качество выносливости, 31 – качество силы, 10 – качество скорости. Средний возраст обследованных 21,75 ± 3,32 года. Среди них – 2 мастера спорта международного класса (МСМК), 25 мастеров спорта (МС), 48 кандидатов в мастера спорта, 29 спортсменов 1 разряда. Компьютерное спирометрическое исследование проведено всем спортсменам на спи- рографическом комплексе «Спироком» (ООО «ХАИ-Медика, г. Харьков) в соответствии с рекомендациями.
Залежність реакцій системи зовнішнього дихання у спортсменів від спрямованості тренувального процесу
Зависимость реакций системы внешнего дыхания у спортсменов от направленности тренировочного процесса
Kanyhina S. M. - ORCID ID: 0000-0002-8197-299X
Keywords: athletes; respiration; physical endurance; strength; speed; спортсмени; функція зовнішнього дихання; витривалість; сила; швидкість; спортсмены; функция внешнего дыхания; выносливость; скорость